Longer Left Ventricular Electric Delay Reduces Mitral Regurgitation After Cardiac Resynchronization Therapy: Mechanistic Insights From the SMART-AV Study (SmartDelay Determined AV Optimization. (November 2016) - Chatterjee, Neal A.; Gold, Michael R.; Waggoner, Alan D.; Picard, Michael H.; Stein, Kenneth M.; Yu, Yinghong; Meyer, Timothy E.; Wold, Nicholas; Ellenbogen, Kenneth A.; Singh, Jagmeet P.
Abstract : Background—: Mitral regurgitation (MR) is associated with worse survival in those undergoing cardiac resynchronization therapy (CRT). Left ventricular (LV) lead position in CRT may ameliorate mechanisms of MR. We examine the association between a longer LV electric delay (QLV) at the LV stimulation site and MR reduction after CRT. Methods and Results—: QLV was assessed retrospectively in 426 patients enrolled in the SMART-AV study (SmartDelay Determined AV Optimization: A Comparison to Other AV Delay Methods Used in CRT). QLV was defined as the time from QRS onset to the first large peak of the LV electrogram. Linear regression and logistic regression were used to assess the association between baseline QLV and MR reduction at 6 months (absolute change in vena contracta width and odds of ≥1 grade reduction in MR). At baseline, there was no difference in MR grade, LV dyssynchrony, or LV volumes in those with QLV above versus below the median (95 ms). After multivariable adjustment, increasing QLV was an independent predictor of MR reduction at 6 months as reflected by an increased odds of MR response (odds ratio: 1.13 [1.03–1.25]/10 ms increase QLV; P =0.02) and a decrease in vena contracta width ( P <0.001). At 3 months, longer QLV (≥median) was associated with significant decrease in LV end-systolic volume (ΔLV end-systolic volume −28.2±38.9 versus −4.9±33.8 mL, P <0.001). Adjustment for 3-month ΔLV end-systolic volume attenuated the association between QLV and 6-month MR reduction. Conclusions—: In patients undergoing CRT, longer QLV was an independent predictor of MR reduction at 6 months and associated with interval 3-month LV reverse remodeling. These findings provide a mechanistic basis for using an electric-targeting LV lead strategy at the time of CRT implant. Abstract : Supplemental Digital Content is available in the text.